Expression of select mRNA in Thoroughbreds with catastrophic racing injuries. (15th February 2021) - Page, Allen E.; Adam, Emma; Arthur, Rick; Barker, Virginia; Franklin, Forrest; Friedman, Ron; Grande, Timothy; Hardy, Michael; Howard, Bruce; Partridge, Emma; Rutledge, Matthew; Scollay, Mary; et al.
Abstract: Background: The ability to identify horses at risk for catastrophic injuries continues to be a pressing issue for the racing industry, especially given recent events in North America. Objectives: Since most catastrophic injuries occur in areas of existing pathology and this pathology is likely to elicit an inflammatory response, it was hypothesised that analysis of messenger RNA (mRNA) expression would detect significant changes in select genes in horses at risk for a catastrophic injury. Study design: Prospective cohort study. Methods: Five racing jurisdictions across the United States participated in this study. A total of 686 Tempus ® RNA Blood Tube samples were collected for mRNA analysis from 107 catastrophically injured horses, as well as from noninjured horses sampled either prerace (n = 374) or postrace (n = 205). A subset of horses (n = 37) were sampled both prerace and postrace for analysis of expression changes during the postrace period. Results: Of 21 genes analysed via RT‐qPCR, the expression of 12 genes ( ALOX5AP, CD14, IL‐10, IL‐1β, IL‐6, IL‐8, MMP1, PTGS2, TLR4, TNFα, TNFSF13B and VEGFA ) changed significantly within 45 minutes after a race and were excluded. Of the remaining nine genes ( BMP‐2, IGF‐1, IL1RN, MMP2, MMP9, Osteoprotegrin, RANKL, SAA1 and TGFβ ), three genes ( IGF‐1, IL1RN and MMP2 ) were found to be significantly different between catastrophically injured and noninjured horses using multiple logistic regression modelling. Receiver operating characteristic analysis of models, which included mRNA expression, demonstrated sensitivities from 76%‐82% (95% CI: 67%‐93%) and specificities from 84%‐88% (95% CI: 71%‐94%) at the Youden Index. Main limitations: Samples were collected as soon as possible postinjury (within 30 minutes). Conclusions: Analysis of mRNA expression of specific genes in the future may be considered as an economical, accessible and noninvasive means by which horses at risk for catastrophic injury can be identified.